Childhood dyspraxia predicts adult-onset nonaffective–psychosis-spectrum disorder. (5th January 2015) - Schiffman, Jason; Mittal, Vijay; Kline, Emily; Mortensen, Erik L.; Michelsen, Niels; Ekstrøm, Morten; Millman, Zachary B.; Mednick, Sarnoff A.; Sørensen, Holger J.
Abstract: Several neurological variables have been investigated as premorbid biomarkers of vulnerability for schizophrenia and other related disorders. The current study examined whether childhood dyspraxia predicted later adult nonaffective–psychosis-spectrum disorders. From a standardized neurological examination performed with children (aged 10–13) at genetic high risk of schizophrenia and controls, several measures of dyspraxia were used to create a scale composed of face/head dyspraxia, oral articulation, ideomotor dyspraxia (clumsiness), and dressing dyspraxia ( n = 244). Multinomial logistic regression showed higher scores on the dyspraxia scale predict nonaffective–psychosis-spectrum disorders relative to other psychiatric disorders and no mental illness outcomes, even after controlling for genetic risk, χ 2 (4, 244) = 18.61, p < .001. Findings that symptoms of dyspraxia in childhood (reflecting abnormalities spanning functionally distinct brain networks) specifically predict adult nonaffective–psychosis-spectrum disorders are consistent with a theory of abnormal connectivity, and they highlight a marked early-stage vulnerability in the pathophysiology of nonaffective–psychosis-spectrum disorders.